The Assessment of Different Types of Student Work Experience for Vocational Orientation from the Perspective of Students with Learning Disabilities - Hübner, Carina (International Journal of Educational and Life Transitions, 2023)
In order to give all young people the same opportunity to engage with their future career at an early stage, vocational orientation programmes have been revised in all German states over the last ten years. For students with learning disabilities the transition from school to vocational education is however associated with special challenges. Due to their impairment in various developmental areas, the prerequisites for subsequent vocational training are often not in place. Hence, revisions to vocational orientation programmes in North Rhine-Westphalia have included the development of additional programmes for students with learning disabilities to meet their individual needs and facilitate the transition process. These offerings include, among others, various work experience opportunities (three one-day insight days, two or three-week internships and longer-term work placements). A quantitative-empirical study was undertaken. Students were surveyed at the end of Grade 10 (nt1 = 201) and one year after leaving school (nt2 = 80). The results suggest that students value a variety of practical work experiences. Assuming that all practical offers are taken up, the results for the longer-term work placements and the student internships lead to significant differences between the genders. Furthermore, the results reveal who supported students in their search for work experience positions. In this respect, the results provide information about how best to accompany students with special needs in school-based vocational orientation.